High sensitivity cardiac troponin I detection in physiological environment using AlGaN/GaN High Electron Mobility Transistor (HEMT) Biosensors - Sarangadharan, Indu; Regmi, Abiral; Chen, Yen-Wen; Hsu, Chen-Pin; Chen, Pei-chi; Chang, Wen-Hsin; Lee, Geng-Yen; Chyi, Jen-Inn; Shiesh, Shu-Chu; Lee, Gwo-Bin; Wang, Yu-Lin (Biosensors & bioelectronics, 2018)
In this study, we report the development of a high sensitivity assay for the detection of cardiac troponin I using electrical double layer gated high field AlGaN/GaN HEMT biosensor. The unique gating mechanism overcomes the drawback of charge screening seen in traditional FET based biosensors, allowing detection of target proteins in physiological solutions without sample processing steps. Troponin I specific antibody and aptamer are used as receptors. The tests carried out using purified protein solution and clinical serum samples depict high sensitivity, specificity and wide dynamic range (0.006–148ng/mL). No additional wash or sample pre-treatment steps are required, which greatly simplifies the biosensor system. The miniaturized HEMT chip is packaged in a polymer substrate and easily integrated with a portable measurement unit, to carry out quantitative troponin I detection in serum samples with < 2µl sample volume in 5min. The integrated prototype biosensor unit demonstrates the potential of the method as a rapid, inexpensive, high sensitivity CVD biomarker assay. The highly simplified protocols and enhanced sensor performance make our biosensor an ideal choice for point of care diagnostics and personal healthcare systems. •A high sensitivity cardiac Troponin I assay is realized using electrical double layer gated AlGaN/GaN HEMT biosensor.•The unique sensing structure provides high sensitivity and selectivity.•Antibody and aptamer based cardiac Troponin I detection.•A portable biosensor system for cardiac Troponin I detection is realized for applications in point of care testing and personal healthcare.